2019
DOI: 10.29328/journal.jhcr.1001008
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of pure red cell aplasia by varicella zoster virus infection

Abstract: Background: Pure red cell aplasia is characterized by anemia, reticulocytopenia and diminished bone marrow erythroid precursors. It has multifactorial etiology and consequently several therapeutic interventions. Case:In August 2017, a young patient was diagnosed to have pure red cell aplasia. She was given immunosuppressive therapy for approximately two months but this treatment was stopped due to intolerance. Later on she developed herpes zoster infection that was treated with valacyclovir. Subsequently, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Recently, Al-Anazi KA, et al reported reversal of pure red cell aplasia (PRCA) by VZV infection [3]. A patient with BM biopsy proven PRCA was initially treated with immunosuppressive therapy, but this treatment was discontinued due to intolerance reported by the patient.…”
Section: The Reported Benefi Cial Effects Of Varicella Zoster Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Al-Anazi KA, et al reported reversal of pure red cell aplasia (PRCA) by VZV infection [3]. A patient with BM biopsy proven PRCA was initially treated with immunosuppressive therapy, but this treatment was discontinued due to intolerance reported by the patient.…”
Section: The Reported Benefi Cial Effects Of Varicella Zoster Virusmentioning
confidence: 99%
“…A patient with BM biopsy proven PRCA was initially treated with immunosuppressive therapy, but this treatment was discontinued due to intolerance reported by the patient. Two months after stopping cyclosporine-A and prednisolone, the patient developed localized herpes zoster (HZ) infection that was successfully treated with valaciclovir [3]. Six weeks after the VZV infection, Hb level started to increase gradually till the patient became packed red blood cell transfusion independent few months later.…”
Section: The Reported Benefi Cial Effects Of Varicella Zoster Virusmentioning
confidence: 99%
“…Varicella zoster virus (VZV), a double-stranded DNA virus, is a highly contagious human neurotropic virus that belongs to the alpha group of herpes viruses [1][2][3][4]. Primary VZV infection (chickenpox) occurs in childhood then the virus becomes latent in the nerve ganglia [1,[5][6][7].…”
mentioning
confidence: 99%
“…Despite encountering VZV infections in patients with worse expected prognosis, the OS in patients who developed VZV infection was superior to that in patients who never developed the infection [19]. Recently, Al-Anazi KA et al, reported BM biopsy-proven reversal of pure red cell aplasia manifested by a gradual increase in Hb level starting 6 weeks following a localized HZ infection till the Hb level plateaued above 14g/dL fourteen months following the viral infection [4]. Additionally, several studies have demonstrated that VZV infection may trigger chronic graft versus host disease (GVHD) following allogeneic HSCT [20][21][22].…”
mentioning
confidence: 99%
See 1 more Smart Citation